Investigation of thermal, mechanical and dielectrical properties of LiYO2 filled poly(lactic acid) nanocomposites. Issue 8 (17th November 2022) - Shruthi, Subbegowda; Hegde, Vinayakprasanna N.; Jayashankar, Jayaprakash; Karthik, Chimatahalli Shanthakumar; Prashantha, Kalappa; Mallu, Puttaswamappa
Abstract: In recent years, the development of portable electronic devices has increased considerably. Polymers and polymer composites are employed in a variety of industries, from structural materials to electronics, as well as in our daily lives. PLA@LiYO2 nanocomposites films were subsequently fabricated by a simple solution casting at various concentrations for the development of electronic materials. The effective doping and homogeneous dispersion of nanoparticles in PLA polymer is characterized by X-ray Diffraction (XRD) and Scanning Electron Microscopy (SEM), Fourier Transform InfraRed (FTIR) spectrophotometer, Differential scanning calorimetry (DSC), Thermogravimetric analysis (TGA), elastic and dielectric properties of PLA composites films. XRD analysis showed that the crystalline characteristics of the nanocomposites increases with increase in dopant concentration. The FTIR absorption spectra of neat PLA and PLA@LiYO2 nanocomposites are almost equivalent to each other, from TGA analysis there will be less percentage of weight loss in the composite's films as the concentration of the nanocomposites increased into PLA matrix, Moreover, a significant increase in Tg with an increase in NPs content from 0 to 4 wt% was also observed, the different elastic moduli such as E, K and G of PLA + LiYO2 films are indirectly proportional to the addition of LiYO2 in to PLA matrix. The doped PLA nanocomposites exhibit unique negative dielectric constant and AC conductivity.